The use of “Power-Words” in animistic Tugen Worldview in light of biblical perspectives - Kigen, Japeth (KABARAK UNIVERSITY, 2019)
Some of the phenomenological features of the practice of animism in Tugenworldview are the exercise of controlling both physical and spiritual realms, especially in handling stressful life challenges to the “known meaningful” worldview. This can be done by the use the following: words, symbolism, magic, charms, fetishes, witchcraft and sorcery.This paper examines the phenomena of Power- Words which have significant power to exert control of both the physical and spiritual or invisible realm. Power-Words have power beyond the ordinary speech of communicating ideas. It is direct and do not need meditation.The study found out that Power-Words are said to have inherent power to deal with all realms of life. They are used in the animistic worldview for protection, provision and treatment against the exigencies of life experienced in the physical and spiritual world. In the use of Power-Words,the findings observed that a careful application of Power-Words is needed so as to avoid syncretistic attitude that enters biblical worldview from animistic worldview which presupposes the sovereignty of man where he plans what is desirable for oneself in his environment. Man becomes God for himself or become co-equal with God, which is a humanistic attitude of trying to achieve one’s own desired goals. This is a false authority in handling and working out one’s own destiny. This piece of work concludes that God cannot be manipulated in any form or any means. God will not share his glory with man, hence Power-Words used by man without acknowledging the sovereignty of God is contrary to the character and nature of God.
FULL TEXT
Keywords: Worldview, Animism, Words